Ankylosis of the temporomandibular joint and mandibular growth disturbance caused by neglected condylar fracture in childhood - Endrajana Endrajana (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Fractures of the mandibular condyle may lead to complications such as disturbance of occlusal function, internal derangement of the joint, ankylosis and mandibular growth disturbance. When treating young patients with the history of mandible trauma, ankylosis of the temporomandibular joint and mandibular growth disturbance are two most important complications of condyle fracture that should be considered. Purpose: This case report attempts to emphasize the long term complication of neglected condylar fracture in children i.e. ankylosis of the temporomandibular joint and subsequently lead to mandibular growth disturbance. Case: A case of right temporo-mandibular joint ankylosis and mandibular growth disturbance in a 28 years old male patient is presented. He had a history of trauma to the mandible after a traffic accident when he was 8 years old. Since then, he experienced difficulty in mouth opening which eventually developed into severe trismus. Case management: The case was treated surgically with gap and interpositional arthroplasty using Mersilen mesh™. Conclusion: Mandibular fractures involving temporomandibular joint in young children should be examined thoroughly and treated adequately in order to prevent ankylosis of the TMJ and the subsequent mandibular growth disturbance.Latar belakang: Fraktur pada kondilus mandibula dapat menyebabkan beberapa komplikasi berupa: gangguan oklusi, internal derangement sendi, ankilosis serta gangguan pertumbuhan mandibula. Pada perawatan penderita usia muda dengan riwayat trauma pada mandibula, perlu diwaspadai dua macam komplikasi akibat fraktur pada kondilus, yaitu ankilosis sendi temporo mandibula dan adanya gangguan pertumbuhan mandibula. Tujuan: Laporan kasus ini bertujuan untuk menekankan bahwa fraktur kondilus pada anak-anak yang tidak mendapatkan perawatan yang semestinya akan mengakibatkan komplikasi jangka panjang berupa ankilosis sendi temporomandibula yang diikuti dengan gangguan pertumbuhan tulang mandibula. Kasus: Penderita laki-laki umur 28 tahun dengan keadaan tidak dapat membuka mulut dan adanya gangguan pertumbuhan tulang mandibula. Terdapat riwayat trauma pada mandibula akibat kecelakaan lalu lintas saat penderita berumur 8 tahun. Semenjak kecelakaan tersebut penderita merasakan kesulitan membuka mulut dan akhirnya sama sekali tidak dapat membuka mulut. Tatalaksana kasus: Untuk merawat kasus ini dilakukan tindakan pembedahan dengan bius umum yaitu gap arthroplasty dengan memakai Mersilen mesh™ sebagai interposisional graft. Kesimpulan: Fraktur kondilus mandibula pada penderita anak-anak memerlukan pemeriksaan dan perawatan yang adekuat untuk menghindari terjadinya ankilosis sendi temporomandibula dan gangguan pertumbuhan tulang mandibula.